The contribution of microstructure and friction in broaching Ferrite–Pearlite steels. Issue 1 (2020) - Courbon, C.; Arrieta, I.M.; Cabanettes, F.; Rech, J.; Arrazola, P.-J.
Abstract: Ferrite–Pearlite (FP) steels are used in many automotive components. However, their machinability in low cutting speed processes appears to be highly dependent on their metallurgical state. An experimental approach combining broaching and tribological tests under machining-like conditions was developed to determine the key FP features driving machining performance. Fundamental tests were performed on fifteen variants so as to cover a wide range of microstructural properties under dry and lubricated conditions using both uncoated and TiN coated High Speed Steel (HSS) tools. The correlation between the microstructure, tribology and outputs such as machining forces and chip thickness ratio is presented.